Description of two related new species of Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) from Brazil and Colombia - Costa, Vinicius; Almeida, Tais B.; Salles, Frederico F. (Zootaxa, 2019)
Two new species of Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) are described, diagnosed and illustrated based on adults and/or nymphs collected in Brazil and Colombia. Both species share an uncommon genitalia morphology, which includes a long penis that is curved at base and a long styliger plate. In the case of the species from Brazil, which is also described based on nymphs, gills are devoid of the characteristic lateral lobes found in the other species of the genus.